The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1073/pnas.96.13.7467
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of TEL transcription activity by interaction with the ubiquitin-conjugating enzyme UBC9

Abstract: The E-26 transforming specific (ETS)-related gene TEL, also known as ETV6, is involved in a large number of chromosomal rearrangements associated with leukemia and congenital fibrosarcoma. The encoded protein contains two functional domains: a helix-loop-helix (HLH) domain (also known as pointed domain) located at the N terminus and a DNA-binding domain located at the C terminus. The HLH domain is involved in protein-protein interaction with itself and other members of the ETS family of transcription factors s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 36 publications
1
54
1
Order By: Relevance
“…In agreement with our observations, key molecules in the SUMO-1 conjugation system, including SUMO-1, Ubc9, and PIAS, have been shown to modulate the transcriptional activities of p53 (44), androgen receptor (40), aryl hydrocarbon receptor (41), and lymphoid enhancer factor-1 (33) even when these target molecules lacked a major sumoylation site(s) by mutation. Moreover, it has been shown that Ubc9 modulates the transcriptional activity of ETS-1-and TEL-independent of its E2 enzymatic activity (45,46). In view of these reports, a mechanism(s) other than the direct SUMO-1 conjugation to PPARā„ by Ubc9 and PIASxā¤ seem to be important for the regulation of transactivation of PPARā„.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our observations, key molecules in the SUMO-1 conjugation system, including SUMO-1, Ubc9, and PIAS, have been shown to modulate the transcriptional activities of p53 (44), androgen receptor (40), aryl hydrocarbon receptor (41), and lymphoid enhancer factor-1 (33) even when these target molecules lacked a major sumoylation site(s) by mutation. Moreover, it has been shown that Ubc9 modulates the transcriptional activity of ETS-1-and TEL-independent of its E2 enzymatic activity (45,46). In view of these reports, a mechanism(s) other than the direct SUMO-1 conjugation to PPARā„ by Ubc9 and PIASxā¤ seem to be important for the regulation of transactivation of PPARā„.…”
Section: Discussionmentioning
confidence: 99%
“…SUMOylation is necessary for PML to form the nuclear body, where PML collaborates with its functional partners (Shen et al 2006), and interaction with UBC9 and SUMOylation modulates the transcriptional activity and nuclear body assembly of TEL (Chakrabarti et al 1999(Chakrabarti et al , 2000. Abnormalities in SUMO modifying proteins have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The sumoylation of certain key factor(s) such as PML might be crucial for the general mechanism of transcriptional control. Moreover, it was reported that UBC9 modulates transcription by ETS-1 and TEL independent of its enzymatic ability to conjugate them with SUMO-1 (59,60) and that UBC9 mediates the nuclear localization of Vsx-1 without its SUMO-1-conjugating activity (61). Thus, UBC9 may possess some other functions in addition to the role of a SUMO-1-conjugating enzyme.…”
Section: Discussionmentioning
confidence: 99%